Psychometric Properties and Factor Structure of the Malay Autism Spectrum Quotient: Children’s Version - Shazia Iqbal Hashmi; Getrude Cosmas Ah Gang; Agnes Sombuling; Nurul Hudani Md Nawi; Puteri Hayati Megat Ahmad (UniversitI Sains Malaysia, 2021)
Introduction: The Malay autism spectrum quotient, children’s version (AQ-Child) is a translated and reduced version of the autism spectrum disorder (ASD) screening instrument. The aim of this study was to test the reliability and validity of the translated Malay version of the questionnaire. Methods: The instrument is a 41-item Likert scale form parental questionnaire designed to screen ASD among children aged 6 years old–12 years old. It was filled out by the parents of 700 children (children with ASD = 47; typically developing children = 653) who were contacted through five special education schools and seven mainstream primary schools. Results: Findings showed that Malay AQ-Child has an internal consistency of 0.82 as a whole scale for 41-items. Receiver operator characteristic analysis showed that the cut score of 63 for the translated, reduced version of the AQ-Child with 41 items had 99% area (95% confidence interval [CI]) under receiver operating characteristic (ROC) curve, and sensitivity and specificity of 93% and 99%, respectively. As for factor structure, principal component analysis (PCA) showed good loading values for most of the items in the instrument. Conclusion: The translated version of the Malay AQ-Child for screening ASD can further facilitate the process of surveillance and early intervention for children who need it.